2007
DOI: 10.1111/j.1526-4637.2007.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated with Current Smoking Status in Chronic Pain Patients

Abstract: Smoking status in CPPs is associated with some variables that are similar for smoking in the general and psychiatric populations (education, race, alcoholism). However, a number of variables expected to be relevant (e.g., mood disorders) were not associated with smoking status in CPPs. These results may not be generalizable to all CPPs as they are derived from CPPs who are return-to-work candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 38 publications
2
64
1
6
Order By: Relevance
“…The studies showed no frequency of current alcohol use according to smoking status, whereas a significant difference in frequency was observed in the present study and could be the cause for the differing data. In addition, Fishbain et al suggested that current alcohol abuse/dependence could be a potent risk factor for smoking in chronic pain patients, which is compatible with the results of this study [35].…”
Section: Discussionsupporting
confidence: 82%
“…The studies showed no frequency of current alcohol use according to smoking status, whereas a significant difference in frequency was observed in the present study and could be the cause for the differing data. In addition, Fishbain et al suggested that current alcohol abuse/dependence could be a potent risk factor for smoking in chronic pain patients, which is compatible with the results of this study [35].…”
Section: Discussionsupporting
confidence: 82%
“…13 It is a consensus in the literature that smokers and ex-smokers have greater predisposition to develop chronic pain, 9,21 although few studies have evaluated this variable. The analgesic chemical properties of nicotine 4 can partially explain the fact that ex-smokers present a greater prevalence ratio when compared to current smokers. It is also possible that some ex-smokers stopped smoking because they presented an associated disease and it was the cause of the pain, superposing this variable.…”
Section: Discussionmentioning
confidence: 99%
“…11 It is estimated that 7% to 40% of the world's population suffer from chronic pain. 3,4 The causes may be the adopted classifi cation, the conditions in which the studies were developed and pain location. 6 Few population-based papers have investigated factors that are associated with this morbidity, especially using high methodological rigor and in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…1 These demographic characteristics are also observed among smokers who seek care for their painful symptoms. [35][36][37]136,177 Lower socioeconomic status and other psychosocial stressors are also related to a higher prevalence of chronic pain and poorer outcomes. 178 -181 All of these factors may impair the ability of individuals to cope with their pain symptoms and thus contribute to chronic painful states.…”
mentioning
confidence: 99%